2015
DOI: 10.1016/j.jtcvs.2015.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Second stage after initial hybrid palliation for hypoplastic left heart syndrome: Arterial or venous shunt?

Abstract: Both arterial and venous shunts are viable options with mortality and morbidity results comparable to those in the literature. The arterial shunt pathway (2-stage Norwood I) may offer better pulmonary arterial growth than the venous shunt (comprehensive/combined Norwood I and II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This allows for more comprehensive surgery for left ventricle rehabilitation at a later age and at significantly larger size. [8][9][10] In our study, a consecutive group of patients with hypoplastic left heart syndrome and borderline cases was included. All the patients were initially managed with a hybrid procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for more comprehensive surgery for left ventricle rehabilitation at a later age and at significantly larger size. [8][9][10] In our study, a consecutive group of patients with hypoplastic left heart syndrome and borderline cases was included. All the patients were initially managed with a hybrid procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple aspects of our learning curve developed, including a change in qualification criteria, introduction of three-dimensional echocardiography, CT, and nuclear magnetic resonance in initial evaluation and in assessment for timing and nature of further procedures. [23][24][25][26][27] We would consider, however, that the relative haemodynamic stability observed during and immediately after deploying self-expanding stents in the ductus has facilitated a less-morbid recovery period and contributed to higher overall survival at the point of censoring among selfexpanding stent patients (75 versus 56%, p = 0.132).…”
Section: Discussionmentioning
confidence: 99%
“…Other groups did not find significant differences in systemic ventricular function [45,46] but indicated that impaired systolic right ventricular strain and strain rate values may be indicative of a subclinical functional decline that becomes relevant during follow-up [46]. After aortic arch reconstruction, patients with initial hybrid palliation also showed higher arterial resistance but better Nassar [38] Pulmonary artery stent graft baffle instead of arch reconstruction at comprehensive stage II DeCampli [39] arterioventricular coupling compared with primary Norwood patients [47]. Bilateral pulmonary artery banding shows a similar diastolic pulmonary runoff than that seen with modified Blalock-Taussig shunts [42].…”
Section: Postoperative Hemodynamics and Ventricular Functionmentioning
confidence: 93%
“…Nassar and colleagues [38] reported a two-stage Norwood I strategy using a systemic-to-pulmonary arterial shunt for pulmonary blood flow at a time when a comprehensive stage II conversion with a cavopulmonary anastomosis would have been an alternative strategy. The strategy is similar to a deferred Norwood strategy, although patients underwent the Norwood procedure relatively late, at approximately 12 weeks of age.…”
Section: Other Hybrid Variationsmentioning
confidence: 99%
See 1 more Smart Citation